2011
DOI: 10.1080/19373260.2011.567816
|View full text |Cite
|
Sign up to set email alerts
|

Use of bolted steel plates for strengthening of reinforced concrete beams and columns

Abstract: Reinforced concrete structures often need strengthening due to defective construction, having higher loads than those foreseen in the initial design of the structure, or as a result of material deterioration or accidental damage. The need for strengthening concrete structures has become a crucial problem not only in developed countries but also in China and other developing countries. The use of bolted steel plates to retrofit existing RC structural components has been proven experimentally and practically to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…As a variant of this retrofit method, individual steel plates are added to steel and steel-concrete composite beams and steel joints to enhance their capacity. Within the same context, steel plates and beams with I-shaped or U-shaped sections are used to retrofit also reinforced concrete beams [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…As a variant of this retrofit method, individual steel plates are added to steel and steel-concrete composite beams and steel joints to enhance their capacity. Within the same context, steel plates and beams with I-shaped or U-shaped sections are used to retrofit also reinforced concrete beams [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…1. Because the bolts at both ends of the steel plates restrain the end rotations of the plates, the initial lateral displacement (v) of the precambered plate can be approximated by a cosine function (Su et al 2011…”
Section: Initial Precambermentioning
confidence: 99%
“…Ersoy, Suleiman, and Tankut (1993), Takeuti, de Hanai, and Mirmiran (2008) and Giménez, Adam, Ivorra, Moragues et al (2009) found that stress-lagging effects could significantly decrease the ultimate axial load capacity of the strengthened columns. To address this stress-lagging problem, Su, Cheng, Wang, Siu, and Zhu (2011) and Su and Wang (2012) proposed a column decompression approach to strengthen preloaded RC columns under axial compression loading. Five fire-exposed RC columns were also axially strengthened by means of this approach (Wang & Su, 2013a, 2014.…”
Section: Introductionmentioning
confidence: 99%